2015
DOI: 10.1186/s12911-015-0232-9
|View full text |Cite
|
Sign up to set email alerts
|

Measuring patient activation in Italy: Translation, adaptation and validation of the Italian version of the patient activation measure 13 (PAM13-I)

Abstract: BackgroundThe Patient Activation Measure (PAM13) is an instrument that assesses patient knowledge, skills, and confidence for disease self-management. This cross-sectional study was aimed to validate a culturally-adapted Italian Patient Activation Measure (PAM13-I) for patients with chronic conditions.Methods519 chronic patients were involved in the Italian validation study and responded to PAM13-I. The PAM 13 was translated into Italian by a standardized forward-backward translation. Data quality was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 54 publications
7
63
0
Order By: Relevance
“…Both EC‐17 and PAM had low values of missing data and showed good internal consistency. PAM exhibited ceiling effects up to 83% in 10 of 13 questions, and similar results are found in other studies (Graffigna, Barello, Bonanomi, Lozza, & Hibbard, ; Moljord et al, ; Zill et al, ). High ceiling effects reduce the ability to detect changes, and may have influenced the low responsiveness of PAM in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Both EC‐17 and PAM had low values of missing data and showed good internal consistency. PAM exhibited ceiling effects up to 83% in 10 of 13 questions, and similar results are found in other studies (Graffigna, Barello, Bonanomi, Lozza, & Hibbard, ; Moljord et al, ; Zill et al, ). High ceiling effects reduce the ability to detect changes, and may have influenced the low responsiveness of PAM in this study.…”
Section: Discussionsupporting
confidence: 89%
“…The supporting materials used in the program included: the main measures of patient engagement currently available in the scientific literature (i.e., Patient Activation Measure by Hibbard et al, 2005; Patient Health Engagement Scale by Graffigna et al, 2015b), the case studies discussed and memory-aid materials including the scales' scoring system, guidance on changes in patients' needs across the patient engagement levels, and related suggested actions, and scientific articles discussing the evidence base that oriented the program's contents.…”
Section: Methodsmentioning
confidence: 99%
“…Patient activation reflects patients' central role in having the knowledge, skills and confidence to make effective decisions to self-manage their own health and change their behaviour (e.g., in adopting a healthy lifestyle) [23][24][25][26]. It is considered to be the most reliable indicator of the willingness and ability to manage health autonomously [27][28][29]. Previous studies have emphasised that increased patient activation level has been shown to improve self-management behaviours, such as physical activity (PA), diet and medication adherence, in patients with various chronic conditions [25,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%